Music, Dance and Song About Tooth Brushing in The Improvement of Knowledge, Teaching Practices and Dental Cleaning Status Mouth in Children Down Syndrom in SLB Kota Tasikmalaya - Rena Setiana Primawati; Sri Susilawati; Hadyana Sukandar (Jurnal Kesehatan Gigi, 2019)
Music, dance and tooth brushing songs (MUTALAGI) given to children with Down syndrome is a modified dental and oral health education effort that aims to increase knowledge, practice brushing and dental and oral hygiene status. Dental health education using music, dance and songs can provide a deeper message and provide a better learning experience for children with Down syndrome. This study uses a mixed method design with a Sequential Exploratory strategy where researchers use two stages, namely qualitative research to conduct group interviews focused on parents of down syndrome children as the basis for making instruments. Media made by researchers was assessed by 12 experts consists of two music and dance experts, two media experts, two dental health education experts, two child dental health experts and two experts with special needs children. Quantitative research was conducted to test the media for 26 down syndrome children using the one group pretest and posttest approach and tested statistically using the Wilcoxon test, Marginal Homogeneity test and Binomial test.The results showed that music, dance and tooth brushing songs for Down Syndromic children were suitable for use in dental health education, and the results of statistical analysis showed a significant increase in knowledge scores, teeth brushing practices and oral and dental hygiene status before and after treatment, i.e. p 0.001.